Sosialisasi Pencegahan Penyakit Gagal Ginjal Kronik untuk Kewaspadaan Terhadap Penyakit Ginjal di Kecamatan Gandus Palembang - Yofa Anggriani Utama (Jurnal Abdimas Kesehatan (JAK), 2026)
Chronic kidney disease is a global health issue that requires serious attention due to its continuously increasing prevalence. Kidney failure is a disease that occurs as a result of kidney damage. Kidneys that are impaired will not be able to optimally remove toxins and fluids that accumulate in the body, which can lead to complications. The objective of this community service activity is to enhance knowledge about preventing kidney failure through educational outreach to residents in the Gandus subdistrict of Palembang. The activity was conducted on October 11, 2025, with 25 participants. The results showed that prior to the education session, 5 participants (20%) had good knowledge about the prevention of chronic kidney disease and awareness of kidney disease. After the education session, 19 participants (76%) had good knowledge about the prevention of kidney failure